(untitled) (Research, Society and Development, 2021)
Objective: To know the situations of vulnerability experienced by family members/caregivers when receiving the diagnosis of the child’s chronic condition. Methodology: This is exploratory descriptive research with a qualitative approach in which 10 family members/caregivers of children with chronic conditions who were hospitalized in pediatric units in a city in southern Brazil participated. Information was collected through interviews and analyzed using the Thematic Analysis. The research was approved by the Research Ethics Committee at Plataforma Brazil. Results: The presence of ontological, ethical, social and cultural vulnerability was identified. Feelings such as suffering, shock and anguish related to the diagnosis of the chronic condition were revealed, which imposed several difficulties to be faced by family members/caregivers. Conclusion: It was identified that with the diagnosis of the child’s chronic condition, several changes occur in the habits of family members/caregivers, often requiring the family to reorganize its entire structure, from food to its external activities, such as work and socialization.